2022
DOI: 10.1038/s41598-022-08714-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing reliability between 3D imaging and 2D photography for external nasal anthropometry

Abstract: This study investigates and compares the reliability and reproducibility of two facial anthropometric methods about external nasal angles, 3D imaging and conventional 2D photography. 2D photograph images and 3D images about external nose of 30 volunteers were taken using digital camera and Morpheus 3D scanner. To evaluate intra-rater reliability, each images were taken over two different days for each subject by the same researcher. To evaluate inter-rater reliability, another researcher took each images for e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…No less than analysis through conventional two‐dimensional photographs, 3D scanner enables precise and accurate anthropometric measurements 17,18 . In recent study using a 3D scanner identical to that used in our study, it was reported that anthropometric measurements using 3D scanner are as accurate as those using conventional 2D photograph images 19 . In addition, the maintenance of surgical results can be easily quantified through the automatic calculation of the aesthetic features after surgery via a 3D scanner.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…No less than analysis through conventional two‐dimensional photographs, 3D scanner enables precise and accurate anthropometric measurements 17,18 . In recent study using a 3D scanner identical to that used in our study, it was reported that anthropometric measurements using 3D scanner are as accurate as those using conventional 2D photograph images 19 . In addition, the maintenance of surgical results can be easily quantified through the automatic calculation of the aesthetic features after surgery via a 3D scanner.…”
Section: Discussionmentioning
confidence: 76%
“…17,18 In recent study using a 3D scanner identical to that used in our study, it was reported that anthropometric measurements using 3D scanner are as accurate as those using conventional 2D photograph images. 19 In addition, the maintenance of surgical results can be easily quantified through the automatic calculation of the aesthetic features after surgery via a 3D scanner. Recently, studies using 3D scanners have been conducted in the field of rhinoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy and reliability of 3D-photography systems vary, and the cost and lack of portability of these systems can limit their widespread adoption (8). Additionally, the interpretation and use of 3D data requires specialized training and expertise (9). This study aims to compare and determine the applicability and feasibility of three different 3Dphotography systems in clinical practice for imaging the complex geometry of the nose with regard to accuracy, precision, feasibility, and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…T hree-dimensional (3D) scanning-based morphologic analyses of facial structures are becoming more popular in several clinical settings. [1][2][3][4][5][6][7] However, the application has not yet been widely reported in augmentation rhinoplasty. When performing augmentation rhinoplasty, determining the degree of augmentation at each anatomic location from the nasion to the nasal tip is the most challenging part.…”
mentioning
confidence: 99%
“…Three-dimensional (3D) scanning-based morphologic analyses of facial structures are becoming more popular in several clinical settings 1–7 . However, the application has not yet been widely reported in augmentation rhinoplasty.…”
mentioning
confidence: 99%